Assesing Urban Heat Island Impact on Environmental Critically Index in Padang City, Indonesia - Yulia Fitri Harahap; Fitra Armando; Edo Nofriadi; Intan Lestari Mulyaning Tyas (School of Postgraduate Studies, Diponegoro Univer, 2026)
Rapid urbanization and vegetation loss significantly intensify the Urban Heat Island (UHI) effect, escalating ecological vulnerability in tropical coastal cities. This study evaluates the spatial relationship between urban warming and environmental degradation in Padang City, Indonesia—a medium-sized tropical coastal city characterized by rapid development and a sharp topographic transition from coastal lowlands to eastern mountains. Utilizing Landsat 8 satellite imagery (January 2023–January 2024) processed via Google Earth Engine (GEE), this research integrates Land Surface Temperature (LST), Normalized Difference Vegetation Index (NDVI), and built-up indices to map UHI intensity and the Environmental Criticality Index (ECI). The results reveal a stark west-east environmental dichotomy: the highly built-up western coastal lowlands act as intensive urban heat hotspots, exhibiting low NDVI values (down to -0.35), maximum LST values of 33.47°C, and high environmental criticality (covering 6.92% of the total area). Conversely, the eastern mountainous zone naturally mitigates thermal stress due to high forest canopy cover and environmental lapse rate benefits. Statistical analysis confirms a strong positive correlation between ECI and LST (r=0.72), demonstrating that urban overheating directly drives broader environmental degradation. Although limited by a single-year dataset and a lack of in-situ validation, this study provides a novel framework for mapping ecological vulnerability. These findings underscore the urgent need for climate-resilient spatial planning in Padang, including mandatory building-scale blue-green infrastructure (green roofs and walls) in the dense western core and strict enforcement of a minimum 30% green open space (RTH) quota in expanding sub-urban zones.